2015
DOI: 10.3389/fpsyg.2015.01638
|View full text |Cite
|
Sign up to set email alerts
|

Active search for antecedents in cataphoric pronoun resolution

Abstract: Cataphoric dependencies where a pronoun precedes its antecedent appear to call on different mechanisms in language comprehension from forward dependencies where the antecedent precedes the pronoun. Previous research has shown that the resolution of cataphoric dependencies involves predictive processes such as the active search mechanism, which hypothesizes the automatic search for an antecedent immediately after encountering a cataphoric pronoun. The current study employs gender mismatch to investigate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 51 publications
3
22
1
Order By: Relevance
“…Previous studies have tested these specific pronoun-antecedent configurations in English and they measured reading times via different behavioral methods (i.e., self-paced reading and eye-tracking). The ERP study by Pablos et al ( 2015 ) that we discuss here examined what the neural reflections of the GMME were 2 and whether the GMME could be cross-linguistically attested.…”
Section: Test Case 1: Event-related Potential Experiments On Backwardmentioning
confidence: 92%
See 4 more Smart Citations
“…Previous studies have tested these specific pronoun-antecedent configurations in English and they measured reading times via different behavioral methods (i.e., self-paced reading and eye-tracking). The ERP study by Pablos et al ( 2015 ) that we discuss here examined what the neural reflections of the GMME were 2 and whether the GMME could be cross-linguistically attested.…”
Section: Test Case 1: Event-related Potential Experiments On Backwardmentioning
confidence: 92%
“…Pablos et al ( 2015 ) found a significant ERP amplitude difference between the no-constraint conditions in (5) and (6) at the position of the name Suzanne in the antecedent Suzanne Jansen . This difference appeared as an anterior negativity over the 300–420 ms time window, where the no-constraint mismatch condition in (6) was more negative than the no-constraint match condition in (5) at the antecedent position.…”
Section: Test Case 1: Event-related Potential Experiments On Backwardmentioning
confidence: 99%
See 3 more Smart Citations